All‐on‐4® Treatment Concept for the Rehabilitation of the Completely Edentulous Mandible: A 7‐Year Clinical and 5‐Year Radiographic Retrospective Case Series with Risk Assessment for Implant Failure and Marginal Bone Level. (23rd December 2014) - Maló, Paulo; de Araújo Nobre, Miguel; Lopes, Armando; Ferro, Ana; Gravito, Inês
Abstract: Background: Studies are needed to evaluate long‐term outcomes of the All‐on‐4® treatment concept (Nobel Biocare AB) for rehabilitation of edentulous mandibles by assessing marginal bone levels and risk indicators for implant failure. Purpose: To evaluate 7‐year clinical outcomes and 5‐year radiographic outcomes of the All‐on‐4 treatment concept. Materials and Methods: This retrospective case series included patients admitted for implant rehabilitations in the mandible, who were followed for 7 years clinically and 5 years radiographically. Primary outcome measures were cumulative prosthetic and implant survival using patient as the unit of analysis (Kaplan‐Meier product limit estimator). Secondary outcome measure was marginal bone level (MBL) at 5 years. Variables associated with implant failure were analyzed using the Cox proportional hazards regression model to calculate hazard ratios (HRs) with 95% confidence intervals (CIs). Binary logistic regression was used to compute odds ratio (OR) with 95% CIs for variables associated with MBL ≥2.8 mm at 5 years. Results: A total of 324 patients (194 women, 130 men, average age = 58.9 years) were rehabilitated with 1, 296 implants supporting 324 full‐arch fixed immediately loaded mandibular prostheses. Sixty‐four patients (19.8%) were lost to follow‐up. Prosthetic survival was 323/324 (99.7%), and 14 patients lost 18 implants, with an estimated cumulative survival rate of 95.4% at 7 years. Variables associated with implant failure were smoking (HR = 5.28; 95% CI: 1.33, 20.91]) and the learning curve effect (0.69 < HR < 0.33 for more experienced levels). Mean MBL at 5 years was 1.81 mm (95% CI: 1.70, 1.92), and smoking was associated with MBL ≥2.8 mm (OR = 2.4; 95% CI: 1.02, 5.62). Conclusions: The high implant and prosthetic survival rates and excellent MBL outcome confirm the predictability and safety of the All‐on‐4 treatment concept over a longer term than previously reported.